Experimental investigation on the combustion, performance and exhaust emission characteristics of poppy oil biodiesel-diesel dual fuel combustion in a CI engine. (15th November 2020) - Uyumaz, Ahmet; Aydoğan, Bilal; Yılmaz, Emre; Solmaz, Hamit; Aksoy, Fatih; Mutlu, İbrahim; İpci, Duygu; Calam, Alper
Highlights: The detailed combustion analyses of poppy oil biodiesel blends were performed. Poppy oil biodiesel emitted lower CO and soot emissions than those of neat diesel. SFC values of biodiesel-diesel fuel blends were higher than those of neat diesel. ITE decreased with biodiesel fuel blends compared to neat diesel. Abstract: In this study, a single cylinder, four-stroke, naturally aspirated with compression ratio of 18:1 direct injection diesel engine was run with opium poppy oil biodiesel-diesel fuel blends. The effects of diesel and biodiesel-diesel fuel blends were investigated experimentally on combustion, performance and emissions. Experiments were conducted with standard diesel fuel and opium poppy oil biodiesel-diesel fuel blends (OP10 and OP20) at maximum brake torque speed of 2200 rpm and five different engine load including 25%, 50%, 75% and 100%. This study focuses on the detailed performance and combustion analysis with opium poppy biodiesel under different engine load and speeds. Test results showed that in-cylinder presssure and heat release rate increased with the increase of engine load when biodiesel fuel blends were used. ID period increased with the usage of biodiesel. Thermal efficiency decreased by about 5.73% and 13.05% with OP10 and OP20 compared to diesel respectively owing to lower calorific value of opium poppy oil biodiesel at 75% engine load. NOx increased 2.9% and 5.98% with OP10 and OP20 according to diesel at full load. On the contrary, CO decreased 14% and 17.42% with OP10 and OP20 compared to diesel at full load.